HPB P67 Patterns of recurrence after pancreatoduodenectomy for pancreatic cancer and the effect of palliative chemotherapy on survival. (7th December 2022) - Russell, Thomas; Labib, Peter; Aroori, Somaiah
Abstract: Background: Pancreatoduodenectomy (PD) is recommended in fit patients with suspected early pancreatic ductal adenocarcinoma (PDAC) affecting the pancreatic head. Unfortunately, recurrence rates are high and only a minority achieve long-term survival. This study aimed to study the patterns of recurrence in patients who undergo PD for PDAC and investigate the impact of palliative chemotherapy on survival. Methods: Data was extracted from the Recurrence After Whipple's (RAW) study, a multicentre retrospective cohort study of outcomes following PD performed for pancreatic head malignancy (29 centres in 8 countries, n=1, 484). Patients with PDAC who developed recurrence within five years of their operation were identified. The site of recurrence and details of palliative chemotherapy (if any) was recorded for each patient. Overall survival (OS) and time from recurrence to time of death was compared between those that received palliative chemotherapy and those that did not using the Mann-Whitney U test. Results: In total, 885 patients (59.4%) had PDAC. Excluding the 37 patients who died within 90-days, 583 (68.8%) developed recurrent disease within five years (on imaging). The median number of months from time of surgery to time of recurrence was ten months (range: 0–58). Of those with recurrence, 30.4% had local recurrence only, 28.4% had local and distal recurrence, and 41.7% had distant recurrence only. The most common sites of recurrence were the liver (40.7%), the superior mesenteric artery area (33.3%), locoregional lymph nodes (20.2%), the omentum/peritoneum (14.9%), the pancreatic anastomosis site (11.8%), the superior mesenteric vein/portal vein area (10.8%), and the coeliac trunk area (9.4%). Among those with recurrence, 46.1% received palliative chemotherapy. The median number of cycles was four (range: 1–12). Just 41.2% of patients completed their planned course; 28.0% stopped their treatment due to disease progression and 17.4% stopped their treatment due to toxicity. Patients who received palliative chemotherapy had similar median OS to those who did not (both 18 months, p=0.6), however, time from recurrence to time of death was significantly longer in the former (9 vs 3 months, p<0.0001). Conclusions: In our multicentre study, over two thirds of PD patients with PDAC developed disease recurrence within five-years of their operation. Just under half of these received palliative chemotherapy. Time from recurrence to time of death was significantly longer in those who did receive palliative chemotherapy.